1994
DOI: 10.1159/000196342
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar Lavage in the Diagnosis of Peripheral Primary and Secondary Malignant Lung Tumors

Abstract: The success rate of cytological examination of the bronchoalveolar lavage fluid (BALF) in patients with primary or metastatic lung tumors varies considerably according to different authors. In a prospective study, we have tried to establish the sensitivity of BAL in comparison with both transbronchial lung biopsy (TBB) and brushing. BAL was performed in 61 patients with lung malignancies and in 56 patients with nonmalignant lung disease: 39 patients had primary lung cancer, 22 had metastatic spread into the lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 4 publications
2
7
0
Order By: Relevance
“…In the present study, the overall sensitivity of bronchoscopy for the diagnosis of lung neoplasia not visible endoscopically was comparable to previous studies evaluating non‐guided conventional bronchoscopy without transbronchial biopsy (6–33%) . While some studies suggested a global sensitivity of 78% for bronchoscopy in the diagnosis of lung cancer, fluoroscopic guidance was used and transbronchial biopsies were performed in the vast majority of these studies. In addition, some of those series also included endobronchial lesions and benign lesions.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, the overall sensitivity of bronchoscopy for the diagnosis of lung neoplasia not visible endoscopically was comparable to previous studies evaluating non‐guided conventional bronchoscopy without transbronchial biopsy (6–33%) . While some studies suggested a global sensitivity of 78% for bronchoscopy in the diagnosis of lung cancer, fluoroscopic guidance was used and transbronchial biopsies were performed in the vast majority of these studies. In addition, some of those series also included endobronchial lesions and benign lesions.…”
Section: Discussionsupporting
confidence: 84%
“…The overall sensitivity and specificity of sputum and bronchial cytology are about 70–80%. Under optimum conditions, the sensitivity and specificity can be as high as 90% or even more (2, 5, 8).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of the cytologic examination of bronchoalveolar lavage specimens in primary lung cancer has been proved. Bronchoalveolar lavage, an easily performed and well‐tolerated procedure, is considered useful in the routine assessment of patients for cancer (5–7). Moreover, about 75% of lung carcinomas are diagnosed cytologically (2).…”
mentioning
confidence: 99%
“…SVL and aspiration had lower diagnostic yields for visible and non visible lesions, compared with other studies [ 21 , 25 , 33 ]. Studies with bronchoalveolar lavage have had a higher diagnostic yield, possibly due to higher fluid volume [ 22 , 23 ]. The low diagnostic yield might also be explained by the procedure of taking a small sample of 10–20 ml from the fluid aspirated and the lack of wedging the bronchoscope into the affected bronchus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of bronchoscopy in peripheral lesions have shown a great variability in the diagnostic yield, with sensitivity for cancer between 20% and 86% [ 5 - 9 ]. The reported predictors of positive samples have been size [ 6 , 9 - 16 ], location [ 10 , 13 , 14 , 17 ], visible lesion, compression or constriction [ 12 , 18 , 19 ], CT bronchus sign [ 13 , 17 , 20 ], fuzzy or sharp border [ 11 ], the use of a C-arm fluoroscope [ 8 , 21 ], and sampling technique [ 11 , 14 , 15 , 18 , 22 - 29 ]. Many studies were based on bronchoscopies performed by selected investigators in highly specialized centres [ 5 , 8 , 10 , 18 ].…”
Section: Introductionmentioning
confidence: 99%